2017
DOI: 10.1159/000481779
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Anti-Platelet Profiling Reveals a Potent Anti-Aggregatory Effect of CD34+ Progenitor Cell-Derived Late-Outgrowth Endothelial Cells in vitro

Abstract: Background/Aims: Platelets affect endothelial progenitor cell (EPC) functionality, inducing their differentiation into mature endothelial cells. However, it remains to be established whether EPCs can influence platelet functionality. Methods: Mononuclear proangiogenic cells (MPCs) and early outgrowth cells (EOCs) were prepared from peripheral blood mononuclear cells, whereas late-outgrowth endothelial cells (OECs) were prepared from cord blood CD34+ cells. The effect of the above cells and their supernatants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…CD34 þ cells were isolated from human cord blood mononuclear cells using MACS MicroBeads and cultured, as previously described. 26 Briefly, cord blood was collected into a tube containing 20 mM EDTA/phosphate-buffered saline solution as an anticoagulant and mononuclear cells were separated by density gradient centrifugation. Isolation of CD34 þ progenitor cells was performed using the human CD34 MicroBead Kit according to the manufacturer's instructions.…”
Section: Isolation Of Cd34 þ Progenitor Cells and Differentiation Into Oecsmentioning
confidence: 99%
See 3 more Smart Citations
“…CD34 þ cells were isolated from human cord blood mononuclear cells using MACS MicroBeads and cultured, as previously described. 26 Briefly, cord blood was collected into a tube containing 20 mM EDTA/phosphate-buffered saline solution as an anticoagulant and mononuclear cells were separated by density gradient centrifugation. Isolation of CD34 þ progenitor cells was performed using the human CD34 MicroBead Kit according to the manufacturer's instructions.…”
Section: Isolation Of Cd34 þ Progenitor Cells and Differentiation Into Oecsmentioning
confidence: 99%
“…The medium was changed daily for the first 7 to 14 days and every 2 days until the appearance of endothelial colonies, which were cultured until the formation of a confluent monolayer of highly proliferative OECs. Outgrowth endothelial cells were characterized as previously described by our group 26 and others. 27 All experiments of the present work were performed using OECs of passage 3, cultured with EGM-2 Bullet Kit supplemented with 10% FBS until confluent.…”
Section: Isolation Of Cd34 þ Progenitor Cells and Differentiation Into Oecsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo platelet depletion ameliorates atherothrombosis [15][16][17] whilst at the same time it impairs angiogenesis [18,19] and tissue regeneration [20][21][22][23]. Platelets modulate vascular and tissue inflammatory events either through cellular interactions [24][25][26][27][28][29][30][31][32] or through differential releasing of immunomodulatory ligands indirectly regulating the function of other blood and vascular wall cells [33,34]. We have previously shown that platelet-derived stromal cell-derived factor-1 (SDF-1) is critically involved in the chemotaxis and recruitment of blood cells to vascular endothelium controlling vascular inflammation and post-injury tissue healing [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%